Partial fraction expansion based frequency weighted balanced singular perturbation approximation model reduction technique with error bounds - Kumar, Deepak; Haja Mohideen, Ahmad Jazlan; Sreeram, Victor; Togneri, Roberto (Elsevier, 2016)
In this paper a new frequency weighted partial fraction expansion based model reduction technique is developed based on the partial fraction expansion approach. In order to further reduce the frequency weighted approximation error, singular perturbation approximation is incorporated into the algorithm. This technique results in stable reduced order models regardless if single sided or double sided weights are used. Error bounds are also derived for the proposed method. For minimization of the frequency weighted approximation error, free parameters are introduced into the algorithm.